Cover Picture: Safe Synthesis of TKX‐50 Using an Insensitive Intermediate (Prop., Explos., Pyrotech. 11/2019). Issue 11 (8th November 2019) - Lee, Woong Hee; Kwon, Kuktae
Abstract : The cover picture shows TKX‐50 synthesis using an insensitive intermediate. Diazidoglyoxime (DAG) which is an intermediate showed very sensitive properties to external stimuli. Sensitivities of DAG were similar with those of primary explosives. On the other hand, THP‐protected DAG was much more insensitive. In the synthetic step for BTO, deprotection of THP and cyclization proceeded simultaneously to yield BTO. TKX‐50 synthesis was completed from DCG using an insensitive intermediate. More details are discussed in the Full Paper by Woong Hee Lee, and Kuktae Kwon on page 1478 ff.